IDENTIFYING BOOK READING ATTITUDE OF UNIVERSITY STUDENTS - Şükrü BİNGÖL (Fırat University, 2019)
This research has been conducted for the purpose of identifying the book reading attitudes of İnönü University, School of Physical Education and Sports students. In the descriptive type research, all of the population was included in the research scope, without selecting a sample and was completed with 526 students who accepted to participate. As data collection tool, personal information form and "Attitude Scale on Book Reading Habit", developed by Gömleksiz (2004), was used. In our research the Cronbach Alpha reliability coefficient of the scale was found as 0.85. Data were evaluated in the statistical suite software, t-test and ANOVA was used on independent groups for the analysis. p